Role of Diagnostic Laparoscopy in Evaluation of Infertile Women - Akhtarunnessa, -; Chowdhury, TA; Ara, Ismat; Gazi, Md Lutful Karim; Biswas, Banika (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Aims: To find out the magnitude of different types of pelvic pathologies female infertility by laparoscopy. Methods: Nine hundred infertile women who had undergone infertility evaluation by laparoscopy to see the pelvic pathology or evaluation of pelvic organs at a private infertility clinic at Dhaka between January 2002 and October 2004 were studied. Assessment of these patients was carried out carefully before starting the endoscopic procedures. A full history was taken which was followed by thorough general, abdominal and pelvic examinations then Laparoscopy was performed under general anaesthesia . Results: The mean age ranged from 18 to 42 years. Among them 612 (68%) patients were aged between 21 to 30 years. Six hundred and seven (67.44%) patients had primary infertility and 293 (32.56%) had secondary infertility. Laparoscopic findings showed that 610 (67.78%) patients had normal uterus while 390 (31.22%) had abnormalities of uterus. Among them 76 (8.4%) had uterine myomas. Five hundred and seventy four (64%) had normal tubes, 70 (7.8%) had some form of peritubal adhesions and 196 (21.78%) had tubal block, either unilateral or bilateral. Six hundred and sixty seven (74.11%) patients had normal pelvic peritoneum, 148 (16.44%) had pelvic adhesions probably from pelvic inflammatory diseases and 85 (9.45%) had frank endometriosis. Two hundred and eighty nine (32.11%) had normal ovaries, 370 (41.11%) had polycystic ovaries (PCO), 109 (12.11%) had periovarian adhesions 72 (8%) patients had simple ovarian cysts while 19 (2.11%) had endometriotic (chocolate) cysts. Conclusion: Ovarian pathology was the highest pelvic abnormality (41%) followed by tubal pathology 36% and uterine pathology 32%. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(2) : 88-91